The Effect Of Young Coconut Water On Hypertension Sufferers In Baroh Village Montasik District Aceh Besar - Siti Junariah; Nurul Sakdah; Yadi Putra (International Journal of Health Engineering and Technology, 2026)
Hypertension is a condition in which a person's blood pressure rises above normal limits. Young coconut water is an isotonic drink that contains almost all minerals, with the highest potassium (K) content. This study aims to determine the effect of young coconut water on lowering blood pressure in people with hypertension. This study used a quantitative method with a quasi-experimental design of the one-group pretest-posttest type. The population consisted of 60 hypertensive patients, and a sample of 15 people was selected using purposive sampling. The measuring instruments used were observation sheets and sphygmomanometers. This study was conducted in Baroh Village from June 24 to 30, 2025. The results showed a decrease in systolic blood pressure from 150.93 mmHg to 149.93 mmHg and diastolic blood pressure from 80.73 mmHg to 78.20 mmHg with a p-value of 0.000 (p< 0.05), indicating a significant effect. The conclusion is that young coconut water has an effect on hypertensive patients in Baroh Village, Montasik District, Aceh Besar.